Third Summer School of the Laboratory for Studies in Economic Sociology at the National Research University "Higher School of Economics" (HSE) "Russian Economic Sociology: Problems and Strategies of Internationalization" - Максим Евгеньевич Маркин (Journal of Economic Sociology, 2011)
Detailed description in the text